2015
DOI: 10.1016/j.rpped.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de deficiência de vitamina D e fatores associados em mulheres e seus recém‐nascidos no período pós‐parto

Abstract: Objective:To assess the prevalence of vitamin D deficiency and its associated factors in women and their newborns in the postpartum period.Methods:This cross-sectional study evaluated vitamin D deficiency/insufficiency in 226 women and their newborns in Viçosa (Minas Gerais, BR) between December 2011 and November 2012. Cord blood and venous maternal blood were collected to evaluate the following biochemical parameters: vitamin D, alkaline phosphatase, calcium, phosphorus and parathyroid hormone. Poisson regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
10
0
6
Order By: Relevance
“…For younger children, representative data were collected only from Mexico (15th-30th parallel north), where approximately one-quarter of pre-schoolers showed 25(OH)D concentration <50 nmol/l (26) . In Brazil, vitamin D level below sufficiency was found among 29•2 % of newborns from a probabilistic cross-sectional study in the city of Viçosa (20th parallel south; n 226) (4) and among 14•6 % of children <25 months of age in a population-based cross-sectional survey in the western Amazon area (20th parallel south; n 158) (5) . In view of the skin physiology involved in the provision of human vitamin D requirements, latitude may be interpreted as a proxy of exposure to sunlight and UV radiation (9) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For younger children, representative data were collected only from Mexico (15th-30th parallel north), where approximately one-quarter of pre-schoolers showed 25(OH)D concentration <50 nmol/l (26) . In Brazil, vitamin D level below sufficiency was found among 29•2 % of newborns from a probabilistic cross-sectional study in the city of Viçosa (20th parallel south; n 226) (4) and among 14•6 % of children <25 months of age in a population-based cross-sectional survey in the western Amazon area (20th parallel south; n 158) (5) . In view of the skin physiology involved in the provision of human vitamin D requirements, latitude may be interpreted as a proxy of exposure to sunlight and UV radiation (9) .…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, some cross-sectional studies among newborns and infants indicated prevalence of vitamin D <50 nmol/l at about 15-30 % (4,5) , but these investigations were rather small and could not cover participants at diverse latitudes.…”
mentioning
confidence: 99%
“…A placenta contém receptores de vitamina D, produz a enzima que converte a 25(OH)D para a sua forma ativa e aumenta, assim, os níveis de dessa vitamina para o feto. Estudos apontam que em recém-nascidos, os estoques de vitamina D adquiridos da mãe duram até a oitava semana de vida (Prado et al, 2015).…”
Section: Revisãounclassified
“…A deficiência de vitamina D materno-fetal consiste em morbidade frequente na atualidade. Estilo de vida, exposição inadequada ao sol, falta de suplementação de vitamina D para crianças e gestantes e ingestão insuficiente dessa mesma vitamina e/ou de cálcio são responsáveis pela alta prevalência de hipovitaminose em países desenvolvidos e em desenvolvimento (Prado et al, 2015).…”
Section: Introductionunclassified
“…Several lines of evidence suggest that there is a strong association between maternal 25(OH)D levels during pregnancy and newborn 25(OH)D concentrations at birth or in the early neonatal period [238][239][240][241][242]. Novakovic et al reported that maternal circulating 25(OH)D levels were the most significant regulator of neonatal circulating vitamin D concentrations, even over the impact of genetic factors [243].…”
Section: The Association Of Maternal Vitamin D Status and Child Vitammentioning
confidence: 99%